1975
DOI: 10.1007/bf00422822
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of blood and serum protein group characteristics in patients with diabetes

Abstract: In a sample of 1.033 diabetic patients characteristics of 10 group specific systems (ABO, MNS, Rh, P, K and Fy blood groups and Hp, Gc and Gm serum types) were tested in order to verify any association of hereditary group specific traits and diabetes. The patients were subgrouped for sex, seriousness of diabetes, age of manifestation and body type. The frequencies of the group specific traits were statistically compared with those of an appropriate control group using the chi2 test. Resulting from that investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

1986
1986
1995
1995

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 10 publications
2
10
0
Order By: Relevance
“…First, a dose effect is often taken as evidence that an observed association is causal. In our data, An association between RH blood group and diabetes has been reported from Oslo, Norway, by Berg et al 17 and from Germany by Scholz et al 18 Berg et al noted a deficiency of phenotypes containing the R, (CDe) haplotype and an excess of phenotypes containing the R 2 (cDE) haplotype among diabetic subjects whereas Scholz et al observed the opposite pattern. In a population-based study of the type described here, it is not possible to assign specific haplotypes based on individual phenotypes.…”
Section: Discussionsupporting
confidence: 58%
“…First, a dose effect is often taken as evidence that an observed association is causal. In our data, An association between RH blood group and diabetes has been reported from Oslo, Norway, by Berg et al 17 and from Germany by Scholz et al 18 Berg et al noted a deficiency of phenotypes containing the R, (CDe) haplotype and an excess of phenotypes containing the R 2 (cDE) haplotype among diabetic subjects whereas Scholz et al observed the opposite pattern. In a population-based study of the type described here, it is not possible to assign specific haplotypes based on individual phenotypes.…”
Section: Discussionsupporting
confidence: 58%
“…Moreover, it is in the same chromosomal region as, and therefore in possible linkage disequilibrium with, the Rh blood group locus (1p35-31.3 for GLUT1 and 1p36.2-34 for Rh). This close proximity combined with the fact that population associations between Rh phenotype and diabetes have been reported in several populations (59,60), including Mexican Americans from San Antonio (61), suggest that GLUT1 also merits consideration as a candidate gene for type II diabetes.…”
Section: Finding the Diabetes Gene(s): Relationship To Primary-prevenmentioning
confidence: 87%
“…A polymorphism at the LPL locus has been associated recently with hyperinsulinemia, hypertriglyceridemia, and reduced levels of highdensity lipoprotein cholesterol, three components of the so-called insulin resistance syndrome, which is thought to be an antecedent of NIDDM (13). The Rh locus was typed because polymorphisms at this locus have been associated previously with diabetes in at least three different population studies (14)(15)(16). The Rh locus is also near TNFR2, a receptor for tumor necrosis factor-a, a cytokine having important metabolic effects on adipocyte metabolism (17).…”
Section: Methodsmentioning
confidence: 99%